Intestinal targeting type urolithin A water-soluble delivery system as well as preparation method and application thereof
By coating ZIF-8 nanoparticles with a methyl β-glucan-modified layer on the surface of urolithin A, an intestinal-targeted water-soluble urolithin A delivery system was constructed, which solved the problems of water solubility and stability of urolithin A and achieved efficient and stable intestinal delivery and improved bioavailability.
Patent Information
- Application Number
- CN202511664900.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2026-02-06
AI Technical Summary
Urolithiasis A has extremely poor water solubility, making it difficult to be absorbed across the gastrointestinal membrane. It is also sensitive to light and heat, easily degraded during food processing and storage, and has low bioavailability. After oral administration, it is easily inactivated in the acidic environment of the gastrointestinal tract, and has a fast metabolic rate in the body, resulting in low overall bioavailability.
A ZIF-8 nanolattice loaded with urolithin A was formed by ultrasonic mixing of zinc nitrate-polyvinylpyrrolidone and 2-methylimidazolium-urolithin A, followed by stirring. A methyl β-glucan-modified layer was then coated on the surface to construct an intestinal-targeted water-soluble urolithin A delivery system. The porous structure and pH-responsive properties of ZIF-8 were used to achieve efficient and stable delivery of urolithin A.
This study achieved high drug loading and high encapsulation efficiency of urolithin A, enhanced the mucosal permeability and intestinal retention capacity of nanoparticles, improved cellular uptake efficiency, and solved the problems of insufficient stability and bioavailability of urolithin A.
Smart Images

Figure CN121466031A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biopharmaceutical technology, specifically relating to an intestinal-targeted urolithin A water-soluble delivery system, its preparation method, and its application. Background Technology
[0002] Mitochondria, as the cell's "energy factory" and core signaling hub, play a crucial role in maintaining cellular homeostasis through multiple functions, including ATP synthesis, calcium homeostasis regulation, reactive oxygen species (ROS) metabolism, and cell fate regulation. However, redox imbalance caused by mitochondrial dysfunction has been proven to be a core pathological mechanism driving various chronic diseases. Excessive mitochondrial-derived ROS (mtROS) not only directly causes DNA damage, protein carbonylation, and lipid peroxidation in intestinal epithelial cells, disrupting intestinal barrier integrity and increasing permeability, but also activates macrophage M1 polarization, recruits immune cells, and induces dysbiosis, forming a vicious cycle of "oxidative stress-inflammation amplification," ultimately exacerbating the progression of inflammatory bowel disease (IBD), neurodegenerative diseases, and other conditions. Given the key driving role of mtROS in the pathogenesis of intestinal diseases, targeting mitochondrial function repair and enhancing cellular antioxidant defense capabilities have become cutting-edge strategies for the prevention and intervention of intestinal and related metabolic diseases. Against this backdrop, urolithin A (UA), a naturally occurring bioactive molecule produced from ellagic acid through intestinal flora metabolism, stands out due to its unique biological activity. Numerous studies have confirmed that UA can clear damaged mitochondria and optimize respiratory chain function by regulating mitophagy, while simultaneously directly activating antioxidant pathways such as Nrf2, inhibiting excessive mtROS production at its source. Its significant efficacy in anti-aging, intestinal barrier repair, and neuroprotection has been widely validated. With its advantages of "natural source - targeting mitochondria - multiple regulation," UA demonstrates extremely high translational potential in functional food development, health supplement innovation, and drug research for intestinal diseases. However, its inherent limitations severely restrict its clinical application and industrialization. From a physicochemical perspective, UA has extremely poor water solubility, greatly hindering its transmembrane absorption in the gastrointestinal tract; and it is highly sensitive to external factors such as light and heat, easily undergoing chemical degradation during food processing, product storage, and transportation, directly weakening its efficacy. More importantly, UA has extremely low bioavailability after oral administration. On the one hand, it is easily hydrolyzed and inactivated under the acidic environment of the gastrointestinal tract and the action of digestive enzymes; on the other hand, even if a small amount is absorbed, the metabolic rate in the body is relatively fast, resulting in poor plasma pharmacokinetic parameters. The overall bioavailability of UA and its derivative metabolites is significantly low. Summary of the Invention
[0003] To address the aforementioned issues, this invention provides an intestinal-targeted urolithin A water-soluble delivery system, its preparation method, and its applications.
[0004] The specific technical solution of the present invention is as follows.
[0005] The first aspect of this invention provides an intestinal-targeted urolithin A water-soluble delivery system, wherein the intestinal-targeted urolithin A water-soluble delivery system is obtained by ultrasonically mixing and stirring an aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A to obtain ZIF-8 loaded with urolithin A; after adding carboxymethyl β-glucan solution dropwise to the dispersion of ZIF-8 loaded with urolithin A, CaCl2 is added, and a methyl β-glucan modification layer is coated on the surface.
[0006] This invention involves sonicating an aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A separately, followed by mixing and stirring. By pre-dispersing urolithin A and the organic ligand in the organic phase at the molecular level, it enables the drug molecules to be captured and encapsulated in situ and synchronously within the forming nanolattice during subsequent mixing with the metal phase, utilizing the rapid self-assembly kinetics of the ZIF-8 framework. This invention fundamentally solves the precipitation problem caused by the hydrophobicity of urolithin A by combining nanoparticle synthesis and drug loading, achieving far higher encapsulation efficiency and loading uniformity than traditional post-loading methods or one-pot methods.
[0007] A second aspect of the present invention provides a method for preparing the aforementioned intestinal-targeted urolithin A water-soluble delivery system, comprising the following steps: An aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A were sonicated for 5 to 10 minutes, then mixed and stirred at a volume ratio of 1:1 to 2. Alternatively, the methanol solution of 2-methylimidazolium / urolithin A was added dropwise to the aqueous solution of zinc nitrate / polyvinylpyrrolidone at a rate of 1 to 2 drops per second. After centrifugation and drying, ZIF-8 loaded with urolithin A was obtained. The mass-to-volume ratio of zinc nitrate, polyvinylpyrrolidone, and water was 150 mg: 50 mg to 250 mg: 5 mL; the mass-to-volume ratio of 2-methylimidazolium, urolithin A, and methanol was 330 mg: 3 mg to 20 mg: 5 mL. ZIF-8 loaded with urolithin A was ultrasonically dispersed to obtain a dispersion of ZIF-8 loaded with urolithin A. Carboxymethyl β-glucan solution was added dropwise to the dispersion and reacted for 30-60 minutes. After centrifugation and resuspending, CaCl2 solution was added to the resuspended solution until the Ca ion concentration reached 1.5 mM. The mixture was stirred for 1-1.5 hours to obtain the intestinal-targeted water-soluble urolithin A delivery system. Specifically, CaCl2 was slowly added dropwise to the resuspended solution to achieve a final concentration of 1.5 mM. The mixture was stirred at 300-500 rpm for 1.5 hours to avoid violent shearing that could damage the particle structure. The mixture was centrifuged and washed twice with distilled water to remove unadsorbed Ca ions. 2+ .
[0008] In another preferred embodiment, the aqueous solution of zinc nitrate-polyvinylpyrrolidone and the methanol solution of 2-methylimidazolium-urolithin A are mixed and stirred at a temperature of 30°C to 70°C for 5 min to 60 min.
[0009] In another preferred embodiment, the pH of the aqueous solution of zinc nitrate-polyvinylpyrrolidone is 4 to 6.
[0010] In another preferred embodiment, the pH of the zinc nitrate-polyvinylpyrrolidone aqueous solution is adjusted to 4-6 using a 10mM sodium hydroxide solution.
[0011] In another preferred embodiment, the mass ratio of CaCl2 to carboxymethyl β-glucan is 1:24~48.
[0012] The third aspect of this invention provides the application of the aforementioned intestinal-targeted urolithin A water-soluble delivery system in the preparation of antioxidant products.
[0013] In another preferred embodiment, the antioxidant product is one that enhances mitochondrial membrane potential stability and reactive oxygen species scavenging ability.
[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention effectively solves the precipitation problem caused by the hydrophobicity of urolithin A by combining nanoparticle synthesis with drug loading. By sonicating an aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A separately and then mixing and stirring them, urolithin A and the organic ligand are pre-dispersed at the molecular level in the organic phase. Then, through the rapid self-assembly kinetics of the ZIF-8 framework, the drug loading of urolithin A reaches 38.65% and the encapsulation efficiency reaches 6.34%. Attached Figure Description
[0015] Figure 1 Figure 1 shows the synthesis and characterization results of the NPs; where A is the TEM image of UA@ZIF-8, B is the TEM image of UA@ZIF-8@CMG NPs; the scale bar is 200 nm; C is the particle size distribution of different NPs measured by DLS; D is the zeta potential of the nanoparticles; E is the UV-Vis absorption spectrum of UA, UA@ZIF-8, and UA@ZIF-8@CMG; F is the infrared absorption spectrum of UA, ZIF-8, free CMG, UA@ZIF-8, and UA@ZIF-8@CMG; G is the XRD pattern of UA, ZIF-8, free CMG, UA@ZIF-8, and UA@ZIF-8@CMG.
[0016] Figure 2To add a graph showing the effect of different UA qualities on the encapsulation efficiency and loading of UA@ZIF-8, different lowercase letters indicate significant differences between samples. p <0.05), the same applies below.
[0017] Figure 3 The figure shows the effect of system reaction temperature on the encapsulation efficiency and loading of UA@ZIF-8.
[0018] Figure 4 The figure shows the effect of the mixing and dropping rate of the system on the encapsulation efficiency and loading of UA@ZIF-8.
[0019] Figure 5 The effect of droplet height on encapsulation efficiency and loading on the amount of UA@ZIF-8 is shown in the figure.
[0020] Figure 6 The figure shows the effect of different proportions of water and methanol in the reaction system on the encapsulation efficiency and loading of UA@ZIF-8.
[0021] Figure 7 Zn 2+ The effect of the ratio of 2-MIM on the encapsulation efficiency and loading of UA@ZIF-8 is shown in the figure.
[0022] Figure 8 To add the effect of different PVP qualities on the encapsulation efficiency and payload of UA@ZIF-8, a graph was added.
[0023] Figure 9 The figure shows the effect of different pH values on the encapsulation efficiency and loading of UA@ZIF-8 in the reaction system.
[0024] Figure 10 The graph shows the effects of different mixing methods on the encapsulation efficiency and loading capacity of UA@ZIF-8.
[0025] Figure 11 The effect of different UA quality on the encapsulation efficiency and loading capacity of UA@ZIF-8 is shown in the figure.
[0026] Figure 12 Figure 1 shows the experimental results of CCK-8; A shows the toxicity of free UA, UA@ZIF-8 and UA@ZIF-8@CMG nanoparticles to Raw264.7 cells; B shows the toxicity of free UA, UA@ZIF-8 and UA@ZIF-8@CMG nanoparticles to Caco-2 cells.
[0027] Figure 13The following figures illustrate the effects of treatment with free C6, C6@ZIF-8, and C6@ZIF-8@CMG nanoparticles for 12 h on the uptake of RAW264.7 and Caco-2 cells: A is the FM image of RAW264.7 cell uptake (scale bar: 20 μm); B is the flow cytometry histogram of RAW264.7 cells; C is the uptake efficiency of RAW264.7 cells for different nanoparticles, expressed as relative MFI; D is the FM image of Caco-2 cell uptake (scale bar: 20 μm); E is the flow cytometry histogram of Caco-2 cells; and F is the uptake efficiency of Caco-2 cells for different nanoparticles, expressed as relative MFI.
[0028] Figure 14 The image shows the JC-10 fluorescence imaging and intensity statistics of mitochondrial membrane potential; A is the mitochondrial membrane potential fluorescence image of each JC-10 stained preparation before and after H2O2 treatment, with a scale bar of 20 μm; B is the relative fluorescence intensity of red fluorescence; C is the relative fluorescence intensity of green fluorescence.
[0029] Figure 15 Figure A shows the results of fluorescence detection and quantitative analysis of ROS generation in RAW264.7 cells; A represents the intracellular ROS generation in the RAW264.7 cell line determined by DCFH-DA analysis under H2O2 treatment, with a scale bar of 20 μm; B represents the relative amount of ROS generated by measuring DCFH fluorescence intensity.
[0030] Figure 16 This is an analysis diagram of H2O2-induced cell damage. Detailed Implementation
[0031] The technical solutions of this invention will be clearly and completely described in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0032] Unless otherwise specified, the methods described in the various embodiments of this invention are conventional methods. Unless otherwise specified, the materials and reagents used are commercially available.
[0033] This invention constructs a carboxymethyl β-glucan-modified UA@ZIF-8@CMG, an intestinal-targeted urolithin A water-soluble delivery system, aiming to achieve efficient, stable, and intelligent delivery of UA. Using ZIF-8 as the core carrier, its porous structure achieves high drug loading and encapsulation of UA, and its pH-responsive properties control UA release in the intestinal environment. A methyl β-glucan-modified (CMG) coating is introduced to enhance the mucosal permeability and intestinal retention capacity of the nanoparticles, while its Dectin-1 ligand properties actively target macrophages, improving cellular uptake efficiency. The system characterizes the physicochemical properties of the nanoparticles, including particle size, zeta potential, encapsulation efficiency, and drug loading. Its biocompatibility, uptake mechanism, and functional output (mitochondrial membrane potential and ROS clearance) are investigated at the RAW264.7 and Caco-2 cell levels. The integrated "protection-targeting-enhancing" delivery system constructed in this invention not only provides a new strategy for solving problems such as low stability, poor targeting and insufficient bioavailability of UA, but also provides new ideas and experimental basis for the precise delivery of natural active ingredients and the development of functional foods.
[0034] Zinc nitrate hexahydrate (Zn(NO3)2·6H2O, 99%), chloroacetic acid (CAA, 99%), 2-methylimidazole (2-MIM, 98%), potassium bromide (Kbr, 99.9%), and β-glucan (100 kDa, purity ≥90%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai). Urolithin A (UA, purity ≥98%) was purchased from Dassef Biotechnology Co., Ltd., and polyvinylpyrrolidone (PVP-K30) and coumarin 6 (C6, 98%) were purchased from Maclean Biochemical Co., Ltd. (Shanghai). Ethanol (EtOH, 99.9%), formic acid (FA, 99%), acetonitrile (ACN, 99.9%), ethyl acetate (EtOAc, 99.5%), and methanol (MeOH, 99.9%) were purchased from Kelon Chemicals Co., Ltd., and lipopolysaccharide (LPS) was purchased from Beijing Solarbio Technology Co., Ltd. (Beijing). Mouse macrophages (RAW264.7 cells) and human colorectal adenocarcinoma cells (Caco-2 cells) were obtained from laboratory-preserved sources. CCK8 and ROS kits were purchased from Beyotime International Co., Ltd. (Shanghai). All other chemicals used in the following examples were of analytical grade.
[0035] The following is a detailed description of an intestinal-targeted urolithin A water-soluble delivery system, its preparation method, and its applications.
[0036] 1. Synthesis of ZIF-8 and UA@ZIF-8 At room temperature, 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of water to obtain an aqueous solution of zinc nitrate-polyvinylpyrrolidone. 330 mg of 2-methylimidazole and UA were dissolved in 5 mL of methanol to obtain a methanol solution of 2-methylimidazole-urolithin A. The aqueous solution of zinc nitrate-polyvinylpyrrolidone and the methanol solution of 2-methylimidazole-urolithin A were mixed, or the methanol solution of 2-methylimidazole / urolithin A was added dropwise to the aqueous solution of zinc nitrate / polyvinylpyrrolidone at a rate of 1 drop / second to 2 drops / second, and stirred magnetically for 3 minutes. The resulting yellow product was centrifuged at 12000 rpm for 15 minutes, washed three times with ethanol, and dried overnight under vacuum to finally obtain UA@ZIF-8. ZIF-8 nanoparticles were used as a control.
[0037] The calculation methods for Encapsulation Efficiency (EE) and Load Capacity (LC) are as follows: Unencapsulated UA was removed from freshly prepared nanoparticles by high-speed centrifugation (12000 rpm, 10 min). The supernatant was then carefully transferred to calculate the encapsulation efficiency. To determine the UA loading, the dried nanoparticles were added to a centrifuge tube containing 10 mL of 1.5% formic acid / methanol. The solution was sonicated for 30 min to completely extract UA. The absorbance of the supernatant was measured at 309 nm using a UV-2600 spectrophotometer, scanning the full wavelength spectrum from 200 to 600 nm to determine the maximum absorption peak. The UA content was determined according to the UA calibration curve. The yield, encapsulation efficiency (EE), and loading (LC) of UA were calculated using the following formulas:
[0038] ; ; ; Where A1 is the amount of UA encapsulated, A2 is the total amount of UA, A3 is the amount of MOF recycled, and A4 is the total amount of UA-MOF.
[0039] 2. Optimization of drug loading in UA@ZIF-8 2.1 Hybrid Mode Optimization Three precursor mixing methods were compared to optimize the synthesis of UA@ZIF-8. All methods were performed at room temperature, and the final products were subjected to centrifugation, washing, and vacuum drying. The three methods are as follows:
[0040] Method A: Sonicate the zinc nitrate-PVP aqueous solution and the 2-methylimidazole-UA methanol solution separately for 5 minutes, then mix them and stir for 30 minutes.
[0041] Method B: First, vortex mix zinc nitrate-PVP aqueous solution with 5 mL of UA methanol solution, then mix this solution with 5 mL of 2-methylimidazole methanol solution (after sonication) and stir.
[0042] Method C: The steps are the same as in B, but UA and 2-methylimidazole are dissolved in 8 mL and 2 mL of methanol, respectively.
[0043] 2.2 PVP dosage To investigate the effect of stabilizer PVP dosage on drug loading, the experiment was conducted at room temperature: First, 150 mg of zinc nitrate and different masses of PVP (0 mg, 50 mg, 150 mg, and 250 mg) were dissolved in 5 mL of deionized water; simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol. Then, the two solutions were mixed and reacted under magnetic stirring for 30 minutes. Finally, the resulting yellow product was collected by centrifugation at 12000 rpm for 15 minutes, washed repeatedly with ethanol, and dried overnight under vacuum to obtain UA@ZIF-8.
[0044] 2.3 Optimization of stirring time To systematically investigate the effect of reaction time on the synthesis of UA@ZIF-8, the experiment was conducted at room temperature. First, 150 mg of zinc nitrate and 150 mg of PVP were dissolved together in 5 mL of deionized water; simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol to form a mixed solution. Then, the two solutions were mixed and reacted under magnetic stirring for 5 min, 10 min, 30 min, and 60 min, respectively. Finally, the reaction product was collected by centrifugation at 12000 rpm for 15 min, washed three times with ethanol, and dried under vacuum overnight to obtain the final product UA@ZIF-8.
[0045] 2.4 Optimization of stirring temperature To evaluate the effect of reaction temperature on the synthesis process, different temperature conditions were set up in the experiment. 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of deionized water; simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol. The mixed solutions were then magnetically stirred at 30 °C, 50 °C, and 70 °C for 30 minutes each. Finally, the product was collected by centrifugation at 12000 rpm for 15 minutes, washed three times with ethanol, and dried under vacuum overnight to obtain UA@ZIF-8.
[0046] 2.5 Methanol:Water system ratio To systematically investigate the effect of solvent composition on the encapsulation effect of urolithin A, synthetic systems with different methanol / water ratios were designed. All operations were performed at room temperature: For the mixed solvent system, 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 2.5 mL, 5 mL, and 7.5 mL of deionized water, respectively; simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 12.5 mL, 10 mL, and 7.5 mL of methanol, respectively. For the pure methanol control system, 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of methanol, while 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol. After mixing all solutions, the reaction was carried out for 30 minutes under magnetic stirring. Finally, the resulting yellow product was collected by centrifugation at 12000 rpm for 15 minutes, washed three times with ethanol, and dried overnight under vacuum.
[0047] 2.6 Dropping height To systematically investigate the effect of the dropper position on the synthesis process, three different experimental conditions were designed. At room temperature, 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of deionized water; simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol. Then, the solution was added dropwise using a dropper under magnetic stirring, with the dropper tip positioned 1 cm below the liquid surface, close to the surface, or 2 cm above the surface. After the addition was complete, the system was stirred continuously for 30 minutes. Finally, the resulting yellow product was collected by centrifugation at 12000 rpm for 15 minutes, washed three times with ethanol, and dried overnight under vacuum.
[0048] 2.7 Solution pH To investigate the effect of pH on the synthesis, the experiment was conducted at room temperature according to the following steps: First, 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of deionized water. Then, the pH of the aqueous phase was adjusted to 4, 5, and 6 using 10 mM sodium hydroxide solution, respectively. Simultaneously, 330 mg of 2-methylimidazole and UA were dissolved in 10 mL of methanol. The two solutions were mixed and reacted under magnetic stirring for 30 minutes. Finally, the resulting yellow product was collected by centrifugation at 12000 rpm for 15 minutes, washed repeatedly with ethanol, and dried overnight under vacuum to obtain UA@ZIF-8.
[0049] 2.8 Zn 2+ Ratio with 2-methylimidazole To systematically investigate the effect of different ratios of zinc precursor to 2-MIM on the encapsulation of UA, the experiment was conducted at room temperature: 150 mg of zinc nitrate and 150 mg of PVP were dissolved in 5 mL of deionized water; simultaneously, 150 mg, 200 mg, and 330 mg of different masses of 2-methylimidazole and UA were dissolved in 10 mL of methanol. The two solutions were mixed and reacted under magnetic stirring for 30 minutes. Finally, the resulting yellow product was collected by centrifugation at 12000 rpm for 15 minutes, washed repeatedly with ethanol several times, and dried overnight under vacuum to obtain UA@ZIF-8.
[0050] 2.9 drop acceleration To investigate the effect of dropping rate on the synthesis, three different conditions were designed. First, two solutions were prepared at room temperature: one was an aqueous solution of 150 mg zinc nitrate and 150 mg PVP dissolved in 5 mL deionized water; the other was a methanol solution of 330 mg 2-methylimidazole and UA dissolved in 10 mL methanol. The key step was to add the methanol solution to the aqueous phase by direct pouring, at a rate of 1 drop / second, or 2 drops / second, respectively, with magnetic stirring. All mixtures were stirred continuously for 30 minutes. Finally, the resulting yellow product was centrifuged at 12000 rpm for 15 minutes, washed three times with ethanol, and dried under vacuum overnight.
[0051] 2.10 UA Addition Amount To systematically evaluate the effect of UA dosage on the drug loading performance of UA@ZIF-8, experiments were conducted based on the optimal reaction conditions obtained from the aforementioned single-factor optimization. The specific steps are as follows: First, zinc nitrate and PVP were dissolved together in 5 mL of deionized water to prepare an aqueous solution; simultaneously, 2-methylimidazole and UA at different masses of 3 mg, 5 mg, 7 mg, 12 mg, 16 mg, and 20 mg were dissolved in 10 mL of methanol. Then, the two solutions were mixed and reacted at room temperature for 10 minutes with magnetic stirring. After the reaction, the resulting yellow product was collected by centrifugation at 12,000 rpm for 15 minutes, and then washed three times with ethanol to remove impurities. Finally, the sample was dried overnight in a vacuum environment to obtain the final product UA@ZIF-8.
[0052] 3. Synthesis of UA@ZIF-8@CMG 1 g of β-glucan was dispersed in 50 mL of isopropanol and stirred continuously at 30 °C for 30 min. Then, 5 mL of 20 wt% sodium hydroxide solution was slowly added dropwise to the β-glucan suspension, and the mixture was stirred for 1 h. Afterward, the temperature of the reaction system was raised to 60 °C, and chloroacetic acid was slowly added to the reaction system, followed by stirring at 60 °C for 3 h. After the reaction was completed, the mixture was cooled to 25 °C in an ice-water bath and neutralized to pH 7.0 with 0.5 M HCl. The crude product was collected by filtration and washed three times with anhydrous ethanol. The washed product was then dissolved in 100 mL of deionized water, filtered to remove impurities, and the filtrate was dialyzed thoroughly with deionized water (Mw cutoff 14000 Da) for 2 days. The dialyzed liquid was collected and freeze-dried to obtain carboxymethylated yeast β-glucan.
[0053] First, urolithin A@ZIF-8 was ultrasonically dispersed. Then, CM-β-glucan solution was added dropwise to the urolithin A@ZIF-8 solution. After stirring for 30 minutes, the mixture was centrifuged at 12000 rpm for 10 minutes to remove unadsorbed CM-β-glucan, and then resuspended in distilled water. Next, 10 mM CaCl2 solution was slowly added dropwise to the resuspended solution, bringing the final concentration to 1.5 mM. The mixture was stirred for 1.5 hours to avoid violent shearing that could damage the particle structure, ultimately yielding UA@ZIF-8@CMG.
[0054] 4. Detection indicators 4.1 Structural Characterization The morphology of the nanoparticles was observed using transmission electron microscopy. A 5 μL dispersion was placed on a carbon-coated copper grid, air-dried, and then observed and TEM images of the sample were acquired at 80 kV. X-ray diffraction (XRD) patterns were obtained using an X-ray diffractometer with a voltage of 40 kV and a current of 40 mA, a 2θ range of 5–35°, and a scan rate of 3° / min. Fourier transform infrared (FTIR) spectra of the samples were acquired using a Fourier transform infrared spectroscopy (FTIR). The dried sample was mixed with potassium bromide at 25 °C and then ground into a uniform fine powder using an agate mortar. The spectral acquisition range was 400–4000 cm⁻¹. -1 The resolution is 4cm. -1 (16 scans / sample). Absorption spectra in the ultraviolet-visible region were studied using a UV-Vis spectrometer. The size, zeta potential, and polydispersity index (PdI) of the nanoparticles were measured using a dynamic light scattering (DLS) / electrophoresis combination. Each sample was measured three times, and the average value was used to check reproducibility.
[0055] 4.2 In vitro cytotoxicity test Cells were incubated with UA, UA@ZIF-8, and UA@ZIF-8@CMG nanoparticles at concentrations of 0 μg / mL, 3.25 μg / mL, 6.25 μg / mL, 12.5 μg / mL, 25 μg / mL, and 50 μg / mL for 12 h. The culture medium was discarded, and the cells were washed twice with PBS. The culture medium was replaced with free-FBS medium containing CCK-8 reagent (10:1), and the cells were co-cultured with the pretreated cells in an incubator for 1 h. Finally, the absorbance was measured using a microplate reader, and the plates were incubated at 37℃, 5% CO2, and saturated humidity for 4 h. The absorbance (OD) value of each well at 450 nm was then measured using a microplate reader. The absorbance values of the blank wells (containing culture medium and CCK-8 solution, but without cells or drugs) were subtracted from the absorbance values of each well. A control well (containing cells, culture medium, and CCK-8 solution, but without drugs) was also set with 100% cell viability. The cell viability of the sample wells was calculated.
[0056] ; Cell viability: cell proliferation activity or cytotoxic activity OD For sample wells: absorbance of wells containing cells, CCK-8 solution, and drug solution.
[0057] OD Blank wells: Absorbance of wells containing culture medium and CCK-8 solution but without cells.
[0058] : Absorbance of pores containing cells and CCK-8 solution but no drug solution.
[0059] 4.3 Cellular uptake Since UA does not fluoresce, an appropriate amount of coumarin 6 (C6) was used to replace UA to synthesize C6@ZIF-8 and C6@ZIF-8@CMG for cellular uptake experiments. RAW264.7 and Caco-2 cells in logarithmic growth phase were used at 3 × 10⁻⁶ cells per well. 5 The sum of 2×10 5Cells were seeded at a density of 3 / 4 cells per well in 6-well plates (n=3) and incubated in an incubator. After 24 hours, the plates were removed and cell morphology and confluence status were observed under a microscope. When cell confluence reached approximately 80%, solutions containing 12.5 μg / mL C6, C6@ZIF-8, and C6@ZIF-8@CMG were added to fresh DMEM serum-free medium, with three replicates per group, and incubated at 37°C for 4 hours. After incubation, the supernatant was aspirated with a pipette, and the cells were washed three times with pre-chilled 1×PBS buffer. 4% paraformaldehyde was added to the wells for fixation at room temperature and in the dark for 15 minutes. Sufficient pre-chilled 1×PBS buffer was added to each well for washing twice. DAPI staining solution was then added for 10 minutes. The cells were then washed three times with pre-chilled 1×PBS buffer and observed under a fluorescence microscope. Simultaneously, FCM was used to quantitatively analyze cell internalization. RAW264.7 and Caco-2 cells were seeded in 6-well plates (3 × 10⁶ cells per well). 5 (N=3 cells) were incubated at 37°C with 5% CO2 in air for 12 hours. Subsequently, the same procedure was performed using fluorescence microscopy. Fluorescence intensity in each well was detected using a BD FACSCelesta™ cell analyzer to quantitatively analyze cellular uptake of the series of carriers.
[0060] 4.4 JC-10 To assess the effects of UA, UA@ZIF-8, and UA@ZIF-8@CMG on mitochondrial function, RAW264.7 cells were seeded and incubated for 24 hours. After treatment with UA, UA@ZIF-8, and UA@ZIF-8@CMG for 24 hours, cells were co-incubated with H2O2 for 5 hours. After washing once with PBS, cells were incubated with JC-10 staining solution for 20 minutes. Following incubation, cells were washed twice with JC-10 staining buffer. Finally, mitochondrial membrane potential was assessed using a fluorescence inverted microscope.
[0061] 4.5 Intracellular reactive oxygen species assay To further determine the effects of UA, UA@ZIF-8, and UA@ZIF-8@CMG on ROS generation, RAW264.7 cells were cultured at a concentration of 3 × 10⁻⁶ cells / year. 5Cells were seeded at a density of 10 cells / well in 24-well plates and incubated for 24 hours. Cells were then treated with 12.5 μg / mL UA, UA@ZIF-8, and UA@ZIF-8@CMG for 5 hours, with negative and positive controls provided. Cells were then washed twice with PBS and treated with 1 mL of DMEM medium containing 20 μM 2′-7′-dichlorodihydrofluorescein diacetate (DCFH-DA) at 37°C for 15 minutes. Cells were then washed twice with PBS and imaged and observed under a fluorescence microscope.
[0062] 5. Results 5.1 Structural Analysis and Characterization TEM images show that the UA@ZIF-8 nanoparticles are rhombic dodecahedral in shape, uniformly distributed throughout the sample, with an average diameter of less than 200 nm. Figure 1 The morphology of A in the sample conforms to the classic nanoparticle morphology of ZIF-8. Furthermore, TEM images of UA@ZIF-8@CMG show that the nanoparticles are spherical and uniformly distributed throughout the sample, with an average diameter of less than 250 nm, larger than that of UA@ZIF-8 nanoparticles; this indicates that carboxymethyl β-glucan was successfully coated on the surface of UA@ZIF-8, as shown in the image. Figure 1 B in. Figure 1 The hydration size and Zeta potential of the nanoparticles are shown. The average hydration size of UA@ZIF-8 is 231.36±6.25 nm, while the average hydration size of UA@ZIF-8@CMG increases to 331.46±2.17 nm. Both have a PDI of less than 0.35. Figure 1 The C in [the text is incomplete and requires further context]. Furthermore, due to the large number of carboxyl groups carried by CMG, the surface charge of the CMG-modified UA@ZIF-8 nanoparticles reversed from 21.6±0.23mV to -23.6±0.35mV for UA@ZIF-8@CMG, as [the text is incomplete and requires further context]. Figure 1 The negative potential of UA indirectly confirms successful loading of UA by Zeta potential analysis. Their negative potential may enhance the stability and biocompatibility of NPs in vivo. Additionally, the particle size estimated by TEM is smaller than that measured by dynamic light scattering, possibly because electron microscopy analyzes air-dried nanoparticles, while DLS analyzes hydrated particle size. Figure 1 The UV-Vis spectrum of UA showed a maximum absorption peak at 309 nm, while the absorption peak of UA@ZIF-8 at 309 nm was significantly reduced, indicating that UA was encapsulated by nanoparticles. Further modification with CMG resulted in a further decrease in absorption peak intensity and a change in peak shape, indicating that the introduction of CMG further affected the UV response of UA.
[0063] Depend on Figure 1 As shown in F in the figure, this infrared spectrum shows UA at 3426.41 cm⁻¹. -1and 3156.6cm -1 For hydroxyl or aromatic CH stretching vibration, 1709.43 cm⁻¹ -1 The value is a carbonyl stretching vibration, 1320.75 cm⁻¹. -1 and 1479.24cm -1 Characteristic peaks are found at the vibrational locations of aromatic skeletons and heterofunctional groups. ZIF-8 shows a peak at 1594.33 cm⁻¹. -1 The C=N stretching vibration of the nearby imidazole ring is typical, and zinc ion coordination affects the vibration in the fingerprint region. (UA@ZIF-8, 1600 cm⁻¹) -1 The characteristic peak is at 1705.66 cm⁻¹. -1 The shift and intensity change of the characteristic peak at the imidazole ring indicate that there is coordination or hydrogen bonding between UA and ZIF-8; the carboxyl group of CMG is asymmetric (1475.47 cm⁻¹). -1 Symmetry (1322.64cm) -1 Stretching vibrations and CO-related vibrations of the sugar ring (1154.71 cm) -1 Its characteristic is that it is 1467.92cm in UA@ZIF–8@CMG. -1 (-COOH) and UA@ZIF-8 in 1596.22cm -1 1705.66cm -1 The changes in characteristic peaks (C=N, C=O, etc.) reflect the binding of CMG and UA@ZIF-8 through coordination of carboxyl and hydroxyl groups, zinc ions, or hydrogen bonds, as well as intermolecular interactions between the sugar ring and the aromatic ring. (3107.54 cm⁻¹) -1 The variations in peak shape and intensity in the region also support hydrogen bond interactions, and the differences in these peaks provide a basis for the interactions between components and the structural evolution of composite materials.
[0064] XRD results are as follows Figure 1 As shown in G, ZIF-8 exhibits multiple sharp characteristic diffraction peaks, typical of metal-organic frameworks (MOFs), demonstrating its high crystallinity. UA displays specific diffraction peaks, reflecting the crystalline phase characteristics of urolithin A itself. CMG shows almost no sharp diffraction peaks, only low-intensity broad peaks, indicating that CMG is an amorphous polymer. Furthermore, UA@ZIF-8 retains the characteristic diffraction peaks of ZIF-8, proving that the ZIF-8 crystal structure is not destroyed, and some characteristic peaks of UA can also be observed, indicating that UA was successfully loaded into ZIF-8 without disrupting its crystallinity. UA@ZIF-8@CMG still retains the characteristic diffraction peaks of ZIF-8, indicating that CMG modification did not destroy the crystal structure of ZIF-8; simultaneously, the subtle changes in peak intensity and their relative proportions originate from the polysaccharide chains of CMG coating the surface of UA@ZIF-8, while the core crystal structure is still preserved.
[0065] 5.2 Optimization of Encapsulation Efficiency (EE) and Drug Loading (LC) 5.2.1 Optimization of stirring time To investigate the effect of stirring time on the performance of the nanodelivery system, the electrical conductivity (EE) and thermal conductivity (LC) were evaluated at four time gradients: 5 min, 10 min, 30 min, and 60 min. The results are as follows: Figure 2 As shown, with increasing stirring time, the encapsulation efficiency first increases and then decreases: it reaches a peak of 38.66% at 10 minutes, and then slightly decreases to 36.51% at 30 minutes. In contrast, the drug loading changes relatively gradually throughout the time range, but reaches its highest value of 4.09% at 10 minutes. In conclusion, the system performs best in terms of both encapsulation efficiency and drug loading when the stirring time is 10 minutes.
[0066] The nucleation and growth of ZIF-8 is a rapid process. A stirring time of 5 minutes is too short, resulting in incomplete nucleation and insufficient framework structure to effectively encapsulate UA, leading to lower EE and LC values. Stirring times of 30 or 60 minutes are too long, causing the formed ZIF-8 nanocrystals to remodel under Ostwald ripening, potentially "squeezing out" some encapsulated UA molecules into the solution, causing a drop in EE and LC from their peak values. 10 minutes is the optimal window for achieving a dynamic balance between nucleation, growth, and drug capture while avoiding over-ripening of the structure.
[0067] 5.2.2 Optimization of stirring temperature To investigate the effect of stirring temperature on the performance of the nanodelivery system, the encapsulation efficiency and drug loading were evaluated at three temperature gradients: 30°C, 50°C, and 70°C. The results are as follows: Figure 3 As shown, the encapsulation efficiency initially increases and then decreases with increasing temperature, reaching a peak of 41.13% at 50°C, and then significantly decreasing to 32.83% at 70°C. In contrast, the drug loading changes relatively more gradually across different temperatures, but its highest value of 4.03% also occurs at 50°C. Therefore, 50°C was determined to be the optimal stirring temperature, under which both encapsulation efficiency and drug loading exhibit the best performance.
[0068] Temperature regulates the synthesis by affecting molecular thermal motion and reaction rate. At 30°C, the reaction kinetics are insufficient, and the crystallinity of ZIF-8 may be poor. 50°C significantly improves the solubility and diffusion rate of UA molecules (in the methanol phase), while accelerating the reaction of Zn. 2+ The coordination reaction with 2-methylimidazole promotes the formation of a denser and more complete ZIF-8 framework, thereby efficiently "locking" more UA inside. Temperatures above 70°C may lead to explosive nucleation growth, resulting in uneven particle size, and may also trigger UA degradation or severe solvent evaporation, which is detrimental to stable loading.
[0069] 5.2.3 Dropping Acceleration The effect of dropping rate on encapsulation efficiency and drug loading was further evaluated, and the results are as follows: Figure 4 As shown, the encapsulation efficiency initially increases and then decreases with decreasing dropping rate, reaching a maximum of 38.23% at 2 drops / second; the lowest encapsulation efficiency is 25.91% under direct mixing conditions. In stark contrast, the drug loading is highest at 10.79% under direct mixing, but significantly decreases to approximately 4% under 1 drop / second and 2 drops / second conditions. In conclusion, 2 drops / second is the optimal condition for achieving a high encapsulation efficiency, while direct mixing is more conducive to achieving a high drug loading.
[0070] This parameter is crucial for controlling the separation of nucleation and growth. Direct mixing leads to instantaneous supersaturation, generating numerous defective and non-uniformly sized nuclei. The drug is excluded by the rapidly depositing framework before it can be effectively captured, resulting in the lowest EE (efficiency). Slow addition at 2 drops / second effectively maintains a moderate precursor supersaturation, allowing for continuous and stable nucleus formation and growth. This provides ample time and opportunity for hydrophobic UA molecules to migrate from the organic phase to the aqueous phase interface and be "in-situ captured" by the growing ZIF-8 framework, thus significantly improving EE.
[0071] 5.2.4 Dropping Height The effect of drop height on encapsulation efficiency and drug loading is as follows: Figure 5 As shown, the highest encapsulation efficiency (43.80%) was achieved when the drug was added at the middle height, while the upper and lower heights corresponded to 42.13% and 39.31%, respectively. Furthermore, the drug loading at the middle height also reached its maximum value of 3.98%. Therefore, the middle dropping height was determined to be the optimal condition, achieving both high encapsulation efficiency and high drug loading.
[0072] The dropping height directly affects the efficiency and uniformity of two-phase fluid mixing. Dropping from above may cause splashing, leading to uneven local concentrations; dropping from below may result in insufficient mixing due to insufficient depth. An intermediate dropping height ensures that the organic phase (containing UA and 2-methylimidazole) mixes with the metal phase (Zn) in the most ideal manner. 2+ This contact allows for optimal mixing at both macroscopic and microscopic scales. This creates an ideal hydrodynamic environment for forming well-dispersed nanoparticles and achieving efficient and uniform loading of UA.
[0073] 5.2.5 Water:Methanol system ratio To investigate the effect of solvent composition, the influence of different water-to-methanol volume ratios on EE and LC was evaluated. Figure 6As shown, the encapsulation efficiency was lowest at 24.67% under pure methanol conditions, significantly improved in a water / methanol mixed solvent, and reached its highest value of 42.33% at a ratio of 1:1, indicating that the introduction of the aqueous phase and its increased proportion help improve the encapsulation effect. In contrast, the drug loading peaked at 4.89% at a ratio of 1:2, higher than the 3.53% achieved under both the 1:1 ratio and pure methanol conditions. Therefore, if encapsulation efficiency is the primary indicator, a 1:1 ratio is optimal; if drug loading is the primary consideration, a 1:2 ratio is better.
[0074] Mechanism Analysis: Pure methanol is a good solvent for UA, but it is unfavorable for the formation of ZIF-8 (a MOF stable in the aqueous phase). Introducing an aqueous phase is crucial: the addition of an aqueous phase reduces the solvent's solubility for UA, making it thermodynamically more likely to be encapsulated by the hydrophobic internal channels of ZIF-8 (i.e., the "anti-solvent effect"). A 1:1 ratio achieves the optimal balance between maintaining sufficient UA solubility to prevent premature precipitation and driving UA partitioning into the ZIF-8 framework, thus resulting in the highest EE. At a 1:2 ratio, the methanol proportion is higher, the total amount of UA dissolved is greater, and the carrier can load more drug before saturation, thus resulting in a higher LC. This precisely reflects the ingenious concept of controlling drug loading behavior through solvent engineering.
[0075] 5.2.6 Zn 2+ Ratio with 2-methylimidazole To investigate Zn 2+ The effect of the molar ratio of 2-methylimidazolium to EE and LC was investigated at ratios of 1:4, 1:6, and 1:8. The results are as follows: Figure 7 As shown, the encapsulation efficiency was highest at a ratio of 1:6 (38.75%), followed by 1:8 (37.88%), and lowest at 1:4 (32.44%). However, the drug loading showed the opposite trend, peaking at 1:4 (5.96%) and decreasing with increasing 2-methylimidazole ratio, reaching 3.88% at 1:6 and 3.51% at 1:8. Therefore, a ratio of 1:6 is most beneficial for improving encapsulation efficiency, while a ratio of 1:4 is most beneficial for increasing drug loading.
[0076] This ratio directly determines the structure and pore characteristics of the ZIF-8 framework. At a 1:4 ratio, the 2-methylimidazole is relatively insufficient, potentially resulting in a loosely structured ZIF-8 with larger pores, allowing for greater physical adsorption of UA (high LC), but poor framework integrity, leading to drug leakage during subsequent processing (low EE). At a 1:8 ratio, the ligand is excessive, potentially causing over-crosslinking of the framework and smaller pores, which is detrimental to UA molecule entry. A 1:6 ratio is most likely to form an ideal ZIF-8 framework with a complete structure and suitable pore size, providing sufficient space to accommodate UA while forming an effective molecular barrier to prevent drug leakage, thus achieving a good balance between EE and LC.
[0077] 5.2.7 PVP Dosage The impact of PVP dosage on EE and LC was further evaluated, and the results are as follows: Figure 8 As shown, the highest encapsulation efficiency of 41.43% was achieved when the PVP dosage was 50 mg; the encapsulation efficiency decreased slightly when the dosage increased to 150 mg; and it slightly rebounded to 38.51% when the dosage further increased to 250 mg. Regarding drug loading, the overall variation was relatively small, with a relatively flat trend, but the highest value of 3.98% also occurred at a PVP dosage of 50 mg. In conclusion, 50 mg is the optimal dosage of PVP, achieving the highest encapsulation efficiency and drug loading.
[0078] As a surfactant, PVP's core function is steric stabilization, controlling nanoparticle size and preventing aggregation. Insufficient dosage (below 50 mg) results in poor stability, increased particle size due to aggregation, reduced specific surface area, and low loading efficiency. Excessive dosage (150 mg or 250 mg) leads to excessively long polymer chains that may not only cover the particle surface but also penetrate and occupy the pore entrances and even internal spaces of ZIF-8, creating steric hindrance and physically preventing UA molecules from entering the carrier, thus causing a decrease in EE and LC. 50 mg represents the optimal balance between effective stabilization and avoiding pore blockage.
[0079] 5.2.8 Solution pH To investigate the effect of pH on EE and LC, conditions ranging from pH 4 to 6 were evaluated. The results are as follows: Figure 9 As shown, both encapsulation efficiency and drug loading are significantly affected by pH, and their trends are consistent. Specifically, when pH is 5, both the encapsulation efficiency (45.41%) and drug loading (4.61%) reach their maximum values. When the pH deviates from this value, rising to 6 or falling to 4, both indicators decrease, reaching their lowest values at pH 4, with an encapsulation efficiency of 39.40% and a drug loading of 3.58%. Therefore, pH 5 is determined to be the optimal condition, most conducive to simultaneously obtaining high encapsulation efficiency and high drug loading.
[0080] pH affects the degree of deprotonation of 2-methylimidazole (pKa ~ 7.0) and Zn. 2+ The form in which H exists. At excessively low pH levels (such as 4), H... + At high concentrations, 2-methylimidazole is difficult to deprotonate, and it reacts with Zn. 2+ Its coordination ability is weak, making ZIF-8 framework formation difficult or incomplete. At excessively high pH levels (such as 6), byproducts such as Zn(OH)2 may be generated, competing with Zn. 2+ pH 5 has been confirmed as the optimal kinetic region for ZIF-8 synthesis, under which 2-methylimidazole exhibits suitable reactivity and can react with Zn. 2+ Rapid and controllable coordination occurs, forming nanocarriers with good crystallinity and strong loading capacity.
[0081] 5.2.9 Hybrid Mode Optimization The effects of three precursor mixing methods on the encapsulation efficiency and drug loading of UA@ZIF-8 were evaluated. Figure 10 As shown, the hybrid method significantly affects both encapsulation efficiency and drug loading capacity. Specifically, method A achieves the highest encapsulation efficiency at 38.65%, followed by method B at 35.78%, while method C achieves the lowest at 32.33%. Correspondingly, method A also achieves the highest drug loading capacity at 6.34%, significantly higher than method B's 4.58% and method C's 3.25%. In conclusion, hybrid method A is determined to be the optimal solution, as it simultaneously achieves the highest encapsulation efficiency and drug loading capacity.
[0082] This result strongly confirms the non-obviousness of the core innovative step of "separate sonication followed by mixing". Method A, namely the separate sonication followed by mixing described in this invention, achieves an in-situ capture mechanism. Methods B and C, which are one-pot methods or mixing methods with different sequences, undoubtedly disrupt this precisely controlled process, leading to the breakdown of the synergistic effect of nucleation, growth, and drug loading. Therefore, both EE and LC are significantly lower than in Method A. This highlights the unique ingenuity and technical advantages of this invention in its mixing strategy.
[0083] 5.2.10 UA Addition Amount Based on the established optimal single-factor reaction conditions, the effects of UA addition amount on the EE and LC of the nanodelivery system were further investigated. Figure 11 As shown, the encapsulation efficiency continuously increased with increasing UA mass, significantly improving from 41.72% at 3 mg to 59.67% at 20 mg, indicating that a higher drug loading contributes to improved encapsulation. In contrast, the drug loading showed a different trend: it peaked at 12.65% at 12 mg, then decreased at 16 mg, and slightly rebounded to 11.99% at 20 mg. This suggests that when the UA addition exceeds 12 mg, the carrier may become saturated, thus limiting or even causing fluctuations in drug loading. In conclusion, increasing the UA mass within the experimental range can significantly improve the encapsulation efficiency; however, to obtain the optimal drug loading, the UA addition should be controlled at approximately 12 mg. This finding provides a crucial basis for precisely optimizing UA-loaded nanocarriers.
[0084] 5.3 Cytotoxicity The toxicity of free UA, UA@ZIF-8, and UA@ZIF-8@CMG nanoparticles to Raw264.7 and Caco-2 cells, such as... Figure 12As shown in Figures A and B, at concentrations of 0–50 μg / mL, free UA, UA@ZIF-8, and UA@ZIF-8@CMG all exhibited dose-dependent effects in both tested cell lines. At low concentrations (0–6.25 μg / mL), UA, UA@ZIF-8, and UA@ZIF-8@CMG showed no significant cytotoxicity to these macrophages after 12 hours of incubation, indicating good cell compatibility. With increasing concentration, the survival rates of Raw264.7 and Caco-2 cells gradually decreased. At all concentrations (0–50 μg / mL), the cytotoxicity of UA@ZIF-8@CMG nanoparticles to Raw264.7 and Caco-2 cells was lower than that of free UA. Notably, in Caco-2 cells, samples with the same nanoparticle concentrations (25 and 50 μg / mL) showed lower cytotoxicity than Raw264.7 cells. This may be due to the lower expression of the Dectin-1 receptor in Caco-2 cells, which could reduce the targeting of CMG in the particles to cells, thereby decreasing cytotoxicity. Macrophages play a crucial role in maintaining intestinal homeostasis and are key cellular components closely related to oxidative stress in IBD progression. Therefore, by adjusting the H2O2 dosage, the optimal concentration for inducing cell damage was determined to be 400 μM. Figure 16 As shown, this laid the foundation for subsequent experiments.
[0085] 5.4 Cellular uptake RAW264.7 cell uptake as follows Figure 13 As shown in Figure A, the green fluorescence of C6@ZIF-8@CMG and C6@ZIF-8 is significantly stronger than that of free C6. This indicates that CMG modification can enhance the internalization of nanoparticles. It suggests that free C6 enters cells via passive diffusion, while the CMG-coated formulation, due to its active targeting effect, more readily recognizes and specifically binds to the Dectin-1 receptor on the surface of RAW264.7 macrophages, potentially improving the targeting efficiency of the ZIF-8 delivery system. Furthermore, the effects of different formulations on RAW264.7 cell uptake were analyzed by flow cytometry. Quantitative data from flow cytometry are shown below. Figure 13 As shown in B and C, compared with the Control group, the uptake of C6, C6@ZIF-8, and C6@ZIF-8 was 2.05 times, 3.04 times, and 3.94 times, respectively. Compared with free C6 and C6@ZIF-8, RAW264.7 cells absorbed more C6@ZIF-8@CMG. These results strongly demonstrate that C6@ZIF-8@CMG effectively enhances cellular uptake of C6 and can specifically enter macrophages through Dectin-1-mediated endocytosis, thereby effectively promoting cellular uptake.
[0086] Caco-2 cell uptake as follows Figure 13 As shown in Figure D, the green fluorescence of C6@ZIF-8 is stronger than that of free C6, while the green fluorescence of C6@ZIF-8@CMG is stronger than that of C6@ZIF-8. These results indicate that CMG modification can enhance the internalization of nanoparticles. Free C6 enters cells via passive diffusion, while C6@ZIF-8@CMG and C6@ZIF-8 nanoparticles enter cells via non-specific endocytosis, suggesting that endocytosis is more readily absorbed by cells than passive diffusion. Furthermore, the uptake capacity of Caco-2 cells for each formulation was analyzed by flow cytometry. Quantitative data from flow cytometry are shown below. Figure 13 As shown in Figures E and F, the uptake of C6, C6@ZIF-8, and C6@ZIF-8@CMG was 2.23 times, 4.65 times, and 7.31 times that of the Control group, respectively. Compared with free C6 and C6@ZIF-8, Caco-2 cells absorbed more C6@ZIF-8@CMG. It has been reported that clathrin-mediated endocytosis allows nanoparticles with an average size of less than 300 nm to penetrate the cell membrane and be non-selectively absorbed. Since both C6@ZIF-8 and C6@ZIF-8@CMG nanoparticles are smaller than 300 nm, the ZIF-8 system nanoparticles may enhance uptake by Caco-2 cells through endocytosis.
[0087] 5.5 Mitochondrial membrane potential (JC-10) analysis H2O2 disrupts the proton gradient balance on the inner mitochondrial membrane through oxidative stress, leading to mitochondrial dysfunction and a decrease in mitochondrial membrane potential (MMP), ultimately causing apoptosis. Urolithin A (UA) is a natural compound that, after oral administration, can induce mitophagy and maintain mitochondrial membrane potential in vitro and in vivo, thereby improving cell function through mitochondrial quality renewal. To investigate whether UA-carried nanoparticles can protect RAW264.7 macrophages from oxidative damage and maintain mitochondrial function, its mitochondrial membrane potential (ΔΨm) level was measured. Figure 14 As shown in Figure A, the H2O2-treated group exhibited the weakest red light and the strongest green light, indicating that H2O2 significantly reduced MMP levels. After intervention with free UA and the UA-carrying system, red light increased significantly. These results are consistent with the quantitative fluorescence intensity analysis results. Figure 14(See B and C in the original text). Notably, the green light intensity of the UA@ZIF-8@CMG treatment group was approximately 2.1 times that of the free UA treatment group and 1.6 times that of the UA@ZIF-8 treatment group, indicating that the UA@ZIF-8@CMG transport system can better maintain MMP levels. This is mainly attributed to the strong affinity of the CMG shell for the Dectin-1 receptor, allowing UA@ZIF-8@CMG to be easily internalized by macrophages via Dectin-1-mediated endocytosis. Subsequently, the complex, once inside the cell, is degraded by a large number of hydrolytic enzymes within the lysosome, first exposing the outer CMG layer and then the inner ZIF-8 core. ZIF-8 disintegrates in the low pH environment of the lysosome, releasing the UA that was originally embedded in the ZIF-8 pores into the lysosomal matrix. Due to the proton sponge effect induced by ZIF-8, the endosome ruptures, and UA can then enter the cytoplasm via diffusion or transporters, ultimately reaching the mitochondria and maintaining the mitochondrial membrane potential.
[0088] 3.6 ROS Generation Mitochondria are organelles located in the cytoplasm outside the cell nucleus and are the core site of intracellular energy production. Besides participating in the regulation of cellular redox potential, they are also responsible for the production of reactive oxygen species (ROS). Therefore, considering the response and scavenging capacity of the UA delivery system to ROS, the DCFH-DA assay was first used to confirm ROS production and oxidative stress; intracellular ROS levels were expressed as the degree of green fluorescence. Figure 15 As shown in Figure A, the DCF fluorescence signal of RAW264.7 cells in the negative control group was weak, indicating limited ROS production. However, when oxidative stress was stimulated with H2O2, the DCF fluorescence signal was significantly enhanced, indicating a significant increase in intracellular ROS levels in RAW264.7 cells. The fluorescence of the free UA group was significantly weaker than that of the H2O2 group, suggesting that free UA can reduce H2O2-induced ROS production through its antioxidant activity. The fluorescence of the UA@ZIF-8 group was further reduced, indicating that ZIF-8-encapsulated UA can exert a more efficient antioxidant effect, which is speculated to be related to the nanocarrier promoting UA uptake by cells. The fluorescence of the UA@ZIF-8@CMG group was the weakest, indicating that the ZIF-8 carrier modified with CMG can further enhance the antioxidant effect of UA, possibly because CMG optimizes the cell targeting and uptake efficiency of the carrier. In addition, quantitative fluorescence analysis (… Figure 15 Figure B) shows that the fluorescence intensity of the H2O2 group was significantly increased by 44 times compared with the control group, confirming its efficient induction of ROS production in RAW264.7 cells; the UA group showed a significant decrease of 9 times compared with the H2O2 group, quantitatively verifying the inhibitory effect of UA; the UA@ZIF-8 group and the UA@ZIF-8@CMG group showed decreases of 16 times and 20 times respectively. These results indicate that the modification of the nanocarrier ZIF-8 with CMG can gradually enhance the antioxidant efficacy of UA, and by optimizing drug delivery, UA can more efficiently scavenge intracellular ROS.
[0089] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0090] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. An intestinal-targeted water-soluble urolithin A delivery system, characterized in that, The intestinal-targeted urolithin A water-soluble delivery system is obtained by sonicating an aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A separately, and then mixing and stirring them to obtain ZIF-8 loaded with urolithin A; carboxymethyl β-glucan solution is added dropwise to the dispersion of ZIF-8 loaded with urolithin A, and then CaCl2 is added to coat the surface with a methyl β-glucan modification layer.
2. A method for preparing the intestinal-targeted urolithin A water-soluble delivery system according to claim 1, characterized in that, Includes the following steps: An aqueous solution of zinc nitrate-polyvinylpyrrolidone and a methanol solution of 2-methylimidazolium-urolithin A were sonicated for 5 to 10 minutes, then mixed and stirred at a volume ratio of 1:1 to 2. Alternatively, the methanol solution of 2-methylimidazolium / urolithin A was added dropwise to the aqueous solution of zinc nitrate / polyvinylpyrrolidone at a rate of 1 to 2 drops per second. After centrifugation and drying, ZIF-8 loaded with urolithin A was obtained. The mass-to-volume ratio of zinc nitrate, polyvinylpyrrolidone, and water was 150 mg: 50 mg to 250 mg: 5 mL; the mass-to-volume ratio of 2-methylimidazolium, urolithin A, and methanol was 330 mg: 3 mg to 20 mg: 5 mL. After ultrasonic dispersion of ZIF-8 loaded with urolithin A, a dispersion of ZIF-8 loaded with urolithin A was obtained. Carboxymethyl β-glucan solution was added dropwise to the dispersion and reacted for 30 min to 60 min. After centrifugation and resuspending, CaCl2 solution was added until the Ca ion concentration reached 1.5 mM. The mixture was stirred for 1 h to 1.5 h to obtain the intestinal-targeted urolithin A water-soluble delivery system.
3. The preparation method according to claim 2, characterized in that, The aqueous solution of zinc nitrate-polyvinylpyrrolidone and the methanol solution of 2-methylimidazolium-urolithin A were mixed and stirred at a temperature of 30℃~70℃ for 5min~60min.
4. The preparation method according to claim 2, characterized in that, The pH value of the aqueous solution of zinc nitrate-polyvinylpyrrolidone is 4-6.
5. The preparation method according to claim 4, characterized in that, The pH of the zinc nitrate-polyvinylpyrrolidone aqueous solution was adjusted to 4-6 using a 10mM sodium hydroxide solution.
6. The preparation method according to claim 2, characterized in that, The mass ratio of CaCl2 to carboxymethyl β-glucan is 1:24~48.
7. The use of the intestinal-targeted urolithin A water-soluble delivery system according to claim 1 in the preparation of antioxidant products.
8. The application according to claim 7, characterized in that, The antioxidant product is designed to enhance mitochondrial membrane potential stability and reactive oxygen species scavenging ability.